Combination of Membrane-Based Pre-Treatment Techniques and Heterogeneous Photocatalysis to Obtain High-Quality Effluents from Produced Water - Greta Brocchetto; Iván Sciscenko; Marco Minella; Lorenzo Craveri; Erica Bertozzi; Marco Malaguti; Marco Coha; Alberto Tiraferri; Davide Vione (Molecules, 2025)
Produced water is the waste aqueous phase from petroleum extraction. As it contains salts, a high organic load, and toxic organic compounds, it should be treated before disposal or reuse. In this research, the combination of membrane processes (microfiltration or membrane distillation) with TiO2-based heterogeneous photocatalysis was assessed to treat synthetic produced water. Pre-treatment with both microfiltration and membrane distillation removed the majority (90–98%) of large organic compounds (humic acids) from produced water. Moreover, membrane distillation also eliminated salt (sodium chloride). However, membrane processes only removed 10–50% of phenol, used here as proxy for low-molecular-weight toxic organic compounds. For this reason, membrane permeates, from microfiltration and membrane distillation, underwent a further photocatalytic treatment aimed at phenol degradation. The application of TiO2 photocatalysis to membrane distillation permeates was successful (100% phenol removal in 5 min), while the high chloride concentration of microfiltration permeates acted as inhibitor of the photocatalytic process. Overall, good-quality water may be obtained from the combination of membrane distillation and heterogeneous photocatalysis, which performed much better than the two techniques used separately. Indeed, while membrane distillation was not able to remove phenol, produced water was too complex a matrix to be effectively treated with TiO2/UV photocatalysis alone.